Women’s Rights and Women in Politics in the Media Coverage of the Polish Parliamentary Election of 2023 by Foreign Media (Politeja, 2025)
The 2023 parliamentary election in Poland was very dynamic, and women’s rights and participation in politics were among the most important topics discussed by domestic experts and media. Many foreign politicians, commentators and journalists followed the election campaign in Poland and discussed the state of Polish democracy. This article aims to present how eight European and international media outlets covered the Polish parliamentary election, especially the subject of women’s rights and participation in politics, and to investigate what kind of image of Poland these media outlets created in their materials. The authors use content analysis and comparative analysis to check whether the abovementioned issues were the subject of coverage by foreign media and, if so, what specific topics were discussed in the materials.